2016
DOI: 10.1111/scs.12328
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in men after prostate cancer surgery: a qualitative interview study

Abstract: Men experience erectile dysfunction as a negative influence on their sexuality with respect to their sex life, sense of self and intimate relations. The dysfunction is thus shown not only to affect sexual life but also to have repercussions for a range of aspects in male intimate life. A broader perspective should be applied in supporting the men's efforts towards improving their quality of life, for example through sexual counselling services performed by nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…Of the 18 articles included, (5)(6)(7)(8)11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 17 were found in the electronic databases and one in the references of the selected studies. In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 18 articles included, (5)(6)(7)(8)11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 17 were found in the electronic databases and one in the references of the selected studies. In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set.…”
Section: Resultsmentioning
confidence: 99%
“…In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set. As for the language of the articles, 16 were published in English, (5,6,8,11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) one in Spanish (7) and one in Portuguese. (23) As for the country where the study was developed, three were developed in Spain, followed by the United States, United Kingdom, Italy, Australia and China, with two studies each, and Brazil, Denmark, Sweden, Norway and The Netherlands, with one study in each country.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Worldwide, prostate cancer (PCa) is among the most prevalent cancer types in men (Huntley et al, 2017; Jakobsson & Fransson, 2013; Jemal et al, 2011; Schantz Laursen, 2017; Siegel et al, 2019). Among men in Norway, 26% of all cancers diagnosed in 2019 were PCa (Cancer Registry of Norway, 2019).…”
Section: Introductionmentioning
confidence: 99%